1999
DOI: 10.1074/jbc.274.43.30963
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin-conjugating Enzymes UbcH7 and UbcH8 Interact with RING Finger/IBR Motif-containing Domains of HHARI and H7-AP1

Abstract: Ubiquitinylation of proteins appears to be mediated by the specific interplay between ubiquitin-conjugating enzymes (E2s) and ubiquitin-protein ligases (E3s). However, cognate E3s and/or substrate proteins have been identified for only a few E2s. To identify proteins that can interact with the human E2 UbcH7, a yeast twohybrid screen was performed. Two proteins were identified and termed human homologue of Drosophila ariadne (HHARI) and UbcH7-associated protein (H7-AP1). Both proteins, which are widely express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
104
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 38 publications
(51 reference statements)
5
104
0
1
Order By: Relevance
“…All three proteins share se- quence similarities with Parkin by the presence of two ring fingers and an IBR domain. HHARI and H7-AP1 were recently shown to interact with the E2 ubiquitin-conjugating enzymes UbcH7 and UbcH8 (29). UIP28 was also recently shown to interact with the E2 ubiquitin-conjugating enzyme UbcM4, which is the mouse homologue of human UbcH8 (30).…”
Section: Resultsmentioning
confidence: 99%
“…All three proteins share se- quence similarities with Parkin by the presence of two ring fingers and an IBR domain. HHARI and H7-AP1 were recently shown to interact with the E2 ubiquitin-conjugating enzymes UbcH7 and UbcH8 (29). UIP28 was also recently shown to interact with the E2 ubiquitin-conjugating enzyme UbcM4, which is the mouse homologue of human UbcH8 (30).…”
Section: Resultsmentioning
confidence: 99%
“…To gain further insight into the function and regulation of ISG15 conjugation, we sought here to identify the E2 enzyme that functions in ISG15 conjugation. Surprisingly, we found that UbcH8, an E2 that functions in Ub conjugation pathways (16)(17)(18)(19)(20)(21)(22), is a major E2 enzyme for the ISG15 conjugation pathway. Therefore, our results indicate that the ISG15 conjugation pathway overlaps or converges with the Ub conjugation pathway at the level of a specific E2 enzyme.…”
mentioning
confidence: 94%
“…UbcH8 has been reported to function as an E2 for several Ub E3 enzymes, including both HECT E3s (16) and RING E3s (17)(18)(19)(20)(21)(22). As an initial test of this hypothesis, we determined whether a UbcH8-competent Ub E3 was capable of conjugating ISG15 to a substrate protein in vitro.…”
Section: Isg15mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to stabilizing and perhaps controlling E2 and substrate interactions, the IBR domain is required to maintain proper RBR domain geometry crucial in recruiting the chaperone Hsp70 (15), a necessary component in many ubiquitination complexes for the presentation of unfolded substrates. In vitro studies with the RBR E3 ligase HHARI have found that UbcH7 binding and subsequent ubiquitination requires both the RING1 domain and the Nterminal portion of the IBR (16).…”
Section: P Arkinson's Disease (Pd) Is a Common Neurodegenerativementioning
confidence: 99%